PENGARUH KETARTILAN MEMBACA AL-QUR’AN TERHADAP KEMAMPUAN MENULIS ARAB MAHASISWA PAI DI STAI MIFTAHUL ULUM TANJUNGPINANG - Zaimah; Neli Hidayah (Miftahul Ulum, 2024)
Al-Qur'an is a way of life for Muslims, both in this world and in the hereafter. In QS. Al-Alaq: 1-5 Allah commands humans, especially a Muslim, to learn to read and write. Both must be balanced between one and the other. However, based on the facts in the field there are some students who are proficient in reading the Qur'an but are still lacking in writing. Vice versa. Therefore, this study aims to determine the skills of PAI students at STAI Miftahul Ulum Tanjungpinang in reading the Koran and their ability to write Arabic. As well as the influence of the ability to read the Qur'an on the ability to write Arabic. This research belongs to the type of quantitative research describing data with numbers or numbers. Methods of data collection by means of tests, namely oral tests and Arabic writing tests, observation, and documentation. While data analysis uses the product moment correlation formula with the help of the Excel application. The results showed that the ability to read the Koran had an average value of 74.03. 43.75% of the total respondents got a low score, 53.125% got a high score, and 3.125% moderately addicted. While the ability to write Arabic the average value obtained is 77.31. The low category is 18.75%, medium; 21.875%, and as high as 59.375%. As for the effect of literacy in reading the Koran on the ability to write Arabic, it obtained a value of Rtable < Rcount, namely 0.063 < 4.00, meaning that Ha was accepted and Ho was rejected which stated that there was an influence between literacy in reading the Koran and the ability to write Arabic in students of PAI STAI Miftahul Ulum Tanjungpinang shows a significant correlation. The significance is 0.59072 which is at the correlation coefficient level of 0.400-0.599 which shows a fairly strong correlation.